Accidental deaths in India in the last decade. (1st March 2011) - Deb, S
Abstract : The objective of the present secondary study was to ascertain the incidence and rates of accidental deaths in India in terms of natural and un-natural causes, gender and age groups. The reported data shows a mixed trend regarding the incidents of accidental deaths during the decade 1997–2007 with an increase of 45.7% in the year 2007 compared to 1997. A total of 3 40 794 accidental deaths were reported in the country during 2007 showing an increase of 8.3% compared to previous year. The percentage of accidental deaths due to causes attributable to nature and those due to un-natural causes were 7.4% and 92.6% respectively. The share of accidental deaths due to causes attributable to nature has increased from 6.8% in 2006 to 7.4% in 2007. The proportion of deaths due to un-natural causes has decreased from 93.2% in 2006 to 92.6% in 2007. Deaths due to causes attributable to nature included avalanche, earthquake, heat stroke and flood. The accidental deaths due to un-natural causes were mainly on account of road accidents (36.3%), railway accidents and rail road accidents (8.3%), drowning (8.6%), poisoning (8.1%), sudden deaths (6.8%) and fire accidents (6.6%). Nearly, 76.7% of the victims of causes attributable to nature were males. Age-wise nearly 6.6% of such victims were up to 14 years of age while 54.4% were in the age group of 15–44 years. Senior citizens (60 years and above) constituted 14.7% of the total victims. The findings suggest a number of measures for prevention of accidental deaths.